A novel mutation (Leu60Pro) in a Chinese pedigree with hereditary factor XI deficiency. Issue 6 (September 2021) - Xie, Haixiao; Liu, Meina; Zou, Anqing; Xie, Yaosheng; Ye, Jiajia
Abstract : N/A: To analyse F11 gene mutations in a Chinese pedigree with hereditary factor XI (FXI) deficiency and investigate the molecular mechanism. The plasma FXI activity and FXI antigen of the proband and the family members were detected by clotting assay and ELISA, respectively. The F11 gene was amplified by PCR and sequenced directly. Online bioinformatics software were needed to analyse the mutations. The proband showed a prolonged activated partial thromboplastin time (93.3 s), whose FXI activity and FXI antigen were low to 2, 4.5%, respectively. A novel mutation c.233T>C (p.Leu60Pro) in exon 4 and a previously described mutation c.1253G>T (Gly400Val) were found in the proband. Protein Leu60 is conserved highly among homologous species. Bioinformatics software indicated that Leu60Pro mutation might affect the protein function. Other coagulation abnormalities were not found. We preliminarily considered the mutations Leu60Pro and Gly400Val were responsible for the decrease FXI level in the family. Leu60Pro mutation in the F11 gene has not been described elsewhere.